An innovative evaluation experience in a high school classroom in the city of Santa Fe- Argentina: meanings and practices (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2019)
The article presents the results of an innovative evaluation experience, carried out in a secondary school oriented in the city of Santa Fe, Argentina, in the curricular space of Ethical and Citizen Training. It is part of the CAI+D 2016: ‘Innovative teaching practices in Geography and History that promote critical thinking’, of the Universidad Nacional del Litoral. The senses given to it are described, analyzed and interpreted, from the point of view of the students involved and the teacher in charge of the course. The work is proposed simultaneously as a narrative of an evaluative experience, as a reflective activity for the students involved, and as a way of reflecting on the teaching practices themselves. It is an invitation for other teachers to write their innovative experiences in various educational contexts, with the deep conviction of the need for the classroom to be transformed into a context of educational research and innovation.
Keywords: innovation; evaluation; meanings; teaching practices; Social Sciences